2019
DOI: 10.1159/000489420
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Metabolic Syndrome and Its Components on Female Sexual Dysfunction: A Narrative Mini-Review

Abstract: Background: The impact of metabolic syndrome on female sexual dysfunction received modest consideration in clinical practice. The aim of the research was to analyze the international literature to determine the relationship between the metabolic syndrome, its components and female sexual disorders. Methods: We identified relevant full-length papers by electronic databases as Index Medicus/Medline, Scopus, Life Science Journals, from 2005 to the present. Studies were searched using the following as search query… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 64 publications
(134 reference statements)
2
18
0
1
Order By: Relevance
“…Consistent with studies in general population ( Schulster et al, 2017 ; Di Francesco et al, 2019 ), we found that subjects with sexual dysfunction had higher HOMA-IR indices than those without sexual dysfunction. However, the underlying mechanisms of how insulin resistance results in sexual dysfunction remain unclear.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with studies in general population ( Schulster et al, 2017 ; Di Francesco et al, 2019 ), we found that subjects with sexual dysfunction had higher HOMA-IR indices than those without sexual dysfunction. However, the underlying mechanisms of how insulin resistance results in sexual dysfunction remain unclear.…”
Section: Discussionsupporting
confidence: 91%
“…Metabolic disturbance is a common adverse reaction in patients with schizophrenia under olanzapine treatment ( Hirsch et al, 2017 ; Lu et al, 2018 ). Several studies reported that metabolic dysfunction is associated with sexual dysfunction in general population ( Schulster et al, 2017 ; Di Francesco et al, 2019 ). But the relationships between metabolic syndrome and sexual dysfunction in patients with schizophrenia have been poorly explored ( Dumontaud et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…All these conditions have been implicated in the pathogenesis of SD. 47 , 48 49 Numerous studies indicate that there is a close relationship between metabolic syndrome and hypothyroidism regardless of overt or subclinical. 50 , 51 52 Therefore, there might be also an association between hypothyroidism and SD.…”
Section: Discussionmentioning
confidence: 99%
“…Di Francesco et al showed that MeTS was associated with a higher prevalence of low sexual desire, orgasm and satisfaction than those without MeTS. 33 Metabolic syndrome has been reported to cause reduced vaginal engorgement via neuropathy and pelvic vascular injury. 34 Excessive adipose tissue accumulation is strongly associated with MeTS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore increased adipogenesis may result in inflammatory, immune and cardiovascular disorders secondary to MeTS. 33 Based on this, it is thought that MeTS may affect female sexual function by disrupting oxygenation by reducing pelvic blood flow through chronic vascular inflammation, oxidative stress and atherosclerosis that can explain the higher rate of FSD in postmenopausal and premenopausal relatively older women. 35 In the present study, logistic regression analysis showed that the Odds ratio between MeTS and FSD was 2.27, which could not reach statistical significance (p = 0.153).…”
Section: Discussionmentioning
confidence: 99%